(3GNJUGQ cJGH GdMjhGfs - (3eMeO Hf ecQe Hf Ydj, CHh GdaVd, LeGd GdOjf GHf efXhQ GdCfUGQj GdQhjaYj GdEaQjbj, J (B711 (3g` s; (3GdLGMXs ((3GdeNJUQ GHf efXhQ s)
(3ChdgG (B:s
(3WGdYJ cJGH GdMjhGf dCHi YKeGf YeQh Hf HMQ GdLGMX hYdbJ eGdGM JYdjbI eSJZaQkG Gddg YR hLd s
(3BNQgG (B:s
(3bGd (B: (3dcfi COQi Cfc QejJ Hg ai HWfc , hGddg MSjHc ai bUI dOYHd Hf Ydi eY Sgd Hf gGQhf fLR GdLRA ced HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(901) s
Keywords: (3GdeYGQa GdYGeIs